Analisis Motivasi Karyawan Divisi Warehouse Di PT. Plasindo Lestari Karawang - Sigit Ardiansyah; Budi Rismayani; Nandang Nandang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to find out, analyze and explain the work motivation of employees in the warehouse division of PT Plasindao Lestari Karawang. The research method uses a qualitative descriptive method while collecting data through primary data from interviews and observations as well as secondary data from various literature and other documents. Data collection techniques were carried out by means of source triangulation, namely through observation, interviews and documentation. Then the collected data were analyzed by means of data reduction, data presentation and drawing conclusions. The research results of PT Plasindo Lestari Karawang apply direct motivation and indirect motivation. Providing positive motivation by PT Plasindo Lestari Karawang is manifested in the form of awards or rewards in accordance with individual performance achievements. Meanwhile, giving negative motivation is done through sanctions such as letters of reprimand or written warnings. The approach taken by PT Plasindo Lestari Karawang in providing motivation to employees is proven to be good and in accordance with theoretical principles. Keywords: work motivation, direct motivation, indirect motivation